(untitled) (Research, Society and Development, 2020)
In Piauí, the Irrigated District Tabuleiros Litorâneos do Piauí (DITALPI) was opened in 1998, an initiative of the government to make agriculture feasible in the region that suffers from low rainfall levels, but which presents significant features for mechanized agriculture. DITALPI was designed to develop according to the stages of the project, so with each new stage completed, the extension of agricultural area expands. With this in mind, the objective of this work was to analyze the land use in the Irrigated District Tabuleiros Litorâneo do Piauí in the years 2000, 2005, 2009, 2015 and 2018. The methodology used was the application of the Normalized Difference Vegetation Index (NDVI), a remote sensing technique that allows the evaluation of the vegetation cover of the soil, on images obtained from the Global Visualization Viewer site (GLOVIS / USGS). The images refer to the Landsat 05 satellite, TM sensor captured on 08/28/2000, 08/10/2005, 08/05/2009 and the Landsat 8 satellite, OLI sensor captured on 08/06/2015 and 28/09/2018. The results obtained show that the area destined to crops has grown in DITALPI, going from 5 685 ha in 2000 to 9 298 ha in 2018, however this growth is presented in a non-linear way, however, this growth is presented in a non-linear manner, considering that from 2000 to 2005 there was no growth, from 2005, through investments from the National Department of Works Against Drought (DNOCS), the agricultural area at DITALPI started to grow in a linear manner in the years 2009, 2015 and 2018.